1988
DOI: 10.1002/aic.690341010
|View full text |Cite
|
Sign up to set email alerts
|

Wrong‐way behavior of packed‐bed reactors: II. Impact of thermal dispersion

Abstract: A sudden reduction in the feed temperature of a packed-bed reactor may lead to a transient temperature rise, referred to as a wrong-way behavior. As expected, the axial dispersion of heat decreases the magnitude of the temperature excursion and prolongs the transient shift to a new steady state. In addition, the thermal dispersion may enable the wrong-way behavior to ignite a low-temperature steady state leading to a disastrous runaway of the reactor. Moreover, it may create a transient high-temperature wave, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 15 publications
4
60
0
Order By: Relevance
“…Consider, for example, a sudden and persistent decrease of feed temperature. The resulting wrong-way response (Boreskov and Slinko, 1965;Pinjala et al, 1988;Luss, 1997) illustrated in Fig. 2a, consists of a transient temperature rise.…”
Section: Introductionmentioning
confidence: 99%
“…Consider, for example, a sudden and persistent decrease of feed temperature. The resulting wrong-way response (Boreskov and Slinko, 1965;Pinjala et al, 1988;Luss, 1997) illustrated in Fig. 2a, consists of a transient temperature rise.…”
Section: Introductionmentioning
confidence: 99%
“…The physical mechanism for thermal spike formation is akin to wrong-way Ž . behavior Oh and Cavendish, 1982;Pinjala et al, 1988 . If the rich fuel persists, thermal runaway can occur quite read- The time elapsed between snapshots of the simulated thermal profile is 1r13 th of a half-cycle.…”
Section: Reverse-flow Reactor Operationmentioning
confidence: 97%
“…In both cases, we have assumed constant wall temperature, constant physical properties and no radial pro"les. According to Pinjala et al (1988) and Chen and Luss (1989), when the inlet variables are changed, if axial dispersion is not taken into account, discontinuities in state variables will be observed, which do not correspond to the physical reality. On the other hand, the terms of axial dispersion allow the transformation of hyperbolic partial di!erential equations into parabolic partial di!erential equations, which are much easier to solve.…”
Section: Mathematical Modelsmentioning
confidence: 99%
“…Metha, Sams and Luss (1981) found analytical criteria to predict that behavior, for zero-order reactions. Pinjala, Chen and Luss (1988) analyzed the importance of the thermal dispersion on the transient response, and concluded that the ignition of the reactor during the transient period is possible to occur. They suggested that axial dispersion terms should be included in the mathematical models, when the transient response of the system is studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation